(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Nutritional beet tubers have different physical and mechanical properties and are suitable for specific working parts of each type of feed grinders with the required level of grinding. Production of hashaki beet tubers using heat treatment in Belarus, Germany, Poland, Australia and other countries is very common. Feed steamers, stirrers, and feed vaporizers are often used to heat Nutritional beet tubers.